EFEKTIVITAS BALI GO LIVE SEBAGAI MEDIA PROMOSI DIGITAL PARIWISATA BALI - Septiani, Ni Luh Putu; Sudiarta, I Nyoman; Wikanatha Sagita, Putu Agus (Jurnal IPTA (Industri Perjalanan Wisata); Vol 7 No 1 (2019): Jurnal IPTA (July 2019), 2019)
The purpose of this research is to know the effectiveness of using Bali Go Live Channel as media promotion digital of Bali Tourism by using EPIC Model approach. Effectiveness measurement is done by obtaining value of empathy dimension, persuation dimension, impact dimension, and communication dimension from digital promotion conducted by Bali Go Live Channel to know how effective promotion is done. Determination of samples in this study using accidental sampling method as much as 100 respondents tourists. Data collection techniques used questionnaires and interviews. Data analysis technique in this research is quantitative descriptive analysis, validity and reliability analysis, simple tabulation analysis, and EPIC Model analysis. From the results of quantitative descriptive analysis can be seen that the measurement of dimensions empathy, dimension persuasion, dimension impact, and dimension communication entered in the range of effective scale. The results of this study show the use of Bali Go Live Channel as a digital promotion media of Bali tourism declared effective. This is shown from the EPIC Rate of 3.98 which fall into the effective category.